10.61533 ANALISIS PENGARUH KOMPETENSI, MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA PERAWAT RAWAT INAP RUMAH SAKIT BAKTI TIMAH PANGKALPINANGTAHUN 2024 - Muslimin; Rizal R. Manullang; Ryan Hasianda Tigor (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
This thesis was conducte$d from November 2024 until January 2025, consisting of 99 pages without appendices. The aim of this research is to determine the influenceof Competence, Work Motivation, and Compensation on the performanceof inpatient nurses at Bakti Timah Hospital Pangkalpinang. The research method used a descriptive quantitative approach. Data were collected by distributing questionnaires to 55 respondents, who were nurses working at Bakti Timah Hospital Pangkalpinang as inpatient nurses. The sample was determined using Probability Sampling with Simple Random Sampling. Data analysis involved Validity Testing, Reliability Testing, Classical Assumption Testing, Multiple Linear Regression Testing, the Coefficient of Determination (R2), Simultaneous Test (F-test), and Partial Test (t-test), processed with the IBM SPSS for Windows Version 26 program. The results of the data analysis showed that competence has a positive and significant effect on the performanceof inpatient nurses with a significance value of 0.000 < 0.05 and t-count (6.189) > t-table (1.675), work motivation has a positive and significant effect on the performanceof inpatient nurses with a significance value of 0.003 < 0.05 and t-count (3.084) > t-table (1.675), and compensation has a positive and significant effect on the performance of inpatient nurses with a significance value of 0.019 < 0.05 and t-count (2.413) > t-table (1.675). Furthermore, simultaneously, competence, work motivation, and compensation have a positive and significant effect on the performanceof inpatie$nt nurses with a significance value of 0.000 < 0.05 and F-count (54.049) > F-table (2.790).